2018
DOI: 10.1016/s2352-3026(18)30018-8
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib, lenalidomide, and rituximab in relapsed or refractory mantle cell lymphoma (PHILEMON): a multicentre, open-label, single-arm, phase 2 trial

Abstract: Janssen and Celgene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 23 publications
5
86
2
Order By: Relevance
“…Patients with high Ki‐67% (>50%) and blastoid cytomorphology had inferior outcomes compared to patients with low Ki‐67% and non‐blastoid cytomorphology. The combination of IR with lenalidomide was also reported from a European phase II multicenter trial with 50 previously treated MCL patients, which demonstrated an ORR of 76% with 56% CR after a median follow up of 17.8 months. In that trial, 38% of patients had grade 3‐4 neutropenia.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 66%
“…Patients with high Ki‐67% (>50%) and blastoid cytomorphology had inferior outcomes compared to patients with low Ki‐67% and non‐blastoid cytomorphology. The combination of IR with lenalidomide was also reported from a European phase II multicenter trial with 50 previously treated MCL patients, which demonstrated an ORR of 76% with 56% CR after a median follow up of 17.8 months. In that trial, 38% of patients had grade 3‐4 neutropenia.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 66%
“…Reduced intensity conditioning allograft as part of frontline consolidation has demonstrated no survival benefit in unselected MCL cohorts [22], though further prospective trials examining TP53-mutated patients are warranted. In contrast, preliminary data incorporating novel agents report (phase II PHILEMON trial combining ibrutinib, lenalidomide, and rituximab in relapsed/refractory patients) a similar PFS for TP53-mutated and unmutated patients [23]. Combination ibrutinib and venetoclax in a small phase II study of heavily pretreated young MCL patients achieved CR in 50% of TP53mutated patients included [24], supporting the potential efficacy of novel agent combinations in this poor-performing group of patients.…”
Section: Treating High-risk Patientsblastoid Variant and Tp53 Alteratmentioning
confidence: 95%
“…This combination also induced an ORR of 95% in untreated FL in a phase 1 trial (NCT01829568), as well as an ORR of 76% (CR 56%) in relapsed or refractory MCL in a phase 2 trial (NCT02460276). 200,201 In untreated CD20 + B-NHLs, ibrutinib plus R-CHOP achieved an ORR of 100% in a phase 1 study (NCT01569750). 202 In addition, in a phase 3 study (NCT01855750) in untreated non-GCB DLBCL, ibrutinib plus R-CHOP produced a CR rate of 67.3%, and placebo plus R-CHOP produced a CR rate of 68.0%, with no statistically significant difference.…”
Section: Bcr-btkmentioning
confidence: 99%